The Roles of Humans and Animals in Selected Southeast Asian Folktales - Simon Arsa Manggala (Universitas Muhammadiyah Semarang, 2023)
In folktales, the main characters are often animals. Choosing animals as the characters could attract children as the tales’ target readers. They are strategically selected as the plots’ point of departure. The depiction of animals should be chosen carefully. Children would find the stories easy to follow if they could find the characters in their surroundings. This paper aims to rigorously examine the linguistic choices employed in some folktales from Brunei Darussalam, Malaysia, Timor Leste, and Vietnam in portraying animals. The folktales are titled The Mighty Babau, The Clever Mousedeer, The Dog and The Hunter, and Heaven’s Uncle Toad. The stories are chosen as the object since animals are prominently mentioned in the stories. Even they appeared in the titles. This paper intends to answer how humans and animals are linguistically depicted. The folktales are analyzed by the thematic structure of the clauses. The analysis centers the discussion on the selection of the verbs, their arguments, and the thematic roles assigned to the arguments. Hypothetically, thematically, the animals in the folktales are assigned significant roles as the Agents. They are the ones doing actions and performing the verbs. On the other hand, human characters are not always depicted as Agents. This paper argues that the thematic structure and roles assigned to animals and humans in the folktales imply their close relationship.